The role of farmer discussion groups in promoting sustainable farming practices: Drivers of participation and environmental impact - Adewale H. Adenuga; Claire Jack (Ecological Indicators)
Farmer discussion groups are increasingly recognised for their role in contributing to economic improvement, however, information relating to their effectiveness in improving environmental performance remains limited. This study investigates the drivers of participation in Environmental Business Development Groups (EBDGs) and evaluates the impact on farm-level environmental performance compared to a profitability-focused Business Development Groups (BDGs). A logistic regression model was used to identify factors influencing EBDG participation, while an Environmental Performance Index (EPI) was constructed to quantify environmental outcomes. Impact evaluation employed Mahalanobis Distance Matching (MDM), with Propensity Score Matching (PSM) applied for robustness. Our results indicate that the farmers’ age, higher educational qualifications, agricultural education, land area farmed, and farm diversification are positive and statistically significant factors influencing participation in EBDGs. Furthermore, membership of the EBDGs has a positive and statistically significant impact on farmers’ environmental performance compared to non-members of any group, with standardised Average Treatment Effect (ATE) and Average Treatment Effect on the Treated (ATT) estimates of 0.67 and 0.63 for EBDGs and 0.53 and 0.47 for BDG, respectively. However, when comparing EBDGs directly to BDGs, no statistically significant difference was found. These results offer valuable insights for policymakers seeking to enhance farmer engagement in environmental programs, highlighting the importance of tailored extension strategies to maximise environmental benefits in the agricultural sector. Encouraging farmer participation in structured discussion groups could be a viable pathway to achieving agricultural sustainability goals.